2012
DOI: 10.1111/j.1365-294x.2012.05639.x
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental selection on transcriptome‐derived SNPs in a high gene flow marine fish, the Atlantic herring (Clupea harengus)

Abstract: High gene flow is considered the norm for most marine organisms and is expected to limit their ability to adapt to local environments. Few studies have directly compared the patterns of differentiation at neutral and selected gene loci in marine organisms. We analysed a transcriptome-derived panel of 281 SNPs in Atlantic herring (Clupea harengus), a highly migratory small pelagic fish, for elucidating neutral and selected genetic variation among populations and to identify candidate genes for environmental ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
263
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(287 citation statements)
references
References 82 publications
9
263
7
Order By: Relevance
“…The candidate gene approach has been used empirically to identify patterns of adaptive genetic variation and disentangle such patterns from neutral genetic population structure (DeFaveri, Jonsson, & Merilä, 2013; Hemmer‐Hansen, Nielsen, Frydenberg, & Loeschke, 2007; Limborg et al., 2012; O'Malley et al., 2010). Candidate genes are selected based on known physiological functions perceived to be of relevance to the study species.…”
Section: Introductionmentioning
confidence: 99%
“…The candidate gene approach has been used empirically to identify patterns of adaptive genetic variation and disentangle such patterns from neutral genetic population structure (DeFaveri, Jonsson, & Merilä, 2013; Hemmer‐Hansen, Nielsen, Frydenberg, & Loeschke, 2007; Limborg et al., 2012; O'Malley et al., 2010). Candidate genes are selected based on known physiological functions perceived to be of relevance to the study species.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, genetic diversity estimated using the fraction of loci at P 95 almost doubled (H E : 0.184) approaching to previous results (Vilas et al., 2015). Anyway, our data suggest that genetic diversity of turbot features in the lower range of values reported for other marine fish studied with SNP panels, such as European sea bass Dicentrarchus labrax (from 0.233 in the Atlantic Ocean to 0.290 in the West Mediterranean Sea; Souche et al., 2015), Atlantic herring ( Clupea harengus ; 0.270–0.310 along the Atlantic Ocean and the Baltic Sea; Limborg et al., 2012), and Asian sea bass ( Lates calcarifer ; 0.292–0.411; Wang, Wan, Lim, & Yue, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…2010), but recent studies have demonstrated the importance of studying genomewide variation for improving estimates of fine‐scale population structure (Sanford and Kelly 2011; Limborg et al. 2012; Milano et al. 2014).…”
Section: Introductionmentioning
confidence: 99%